2017
DOI: 10.1002/pen.24736
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of poly(hexamethylene oxamide) copolymers containing ether moiety

Abstract: To modify the properties of poly(hexamethylene oxamide) (PA62), amine-terminated polyoxypropylene glycols (PGs) were introduced into the polyoxamide main chain as soft segments. A series of PA62/PG2 copolymers were synthesized successfully by a two-step method. Fourier transform infrared spectroscopy, solution proton nuclear magnetic resonance spectroscopy ( 1 H-NMR), differential scanning calorimetry, thermogravimetric analysis, and wide-angle X-ray diffraction were used to analyze the structures and to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 45 publications
1
12
0
1
Order By: Relevance
“…This low saturated water absorption should be mainly attributed to the unique adjacent double hydrogen bonds in POA and high crystallinity of PA62, which gave it a better dimensional stability compared with PA6. Similar behaviors have been also reported in others copolymer of PA62 …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This low saturated water absorption should be mainly attributed to the unique adjacent double hydrogen bonds in POA and high crystallinity of PA62, which gave it a better dimensional stability compared with PA6. Similar behaviors have been also reported in others copolymer of PA62 …”
Section: Resultssupporting
confidence: 91%
“…However, 1,5‐pentamethylene diamine is expensive and unstable in supply in present, limiting its large‐scale application. Preliminary study confirmed that the properties of poly (hexamethylene oxamide) (PA62) copolymers are comparable with PA52, and it is far better than PA46 . The raw materials of PA62 are cheap and easy to obtain.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, much research on polyoxamides has been reported by utilizing this two-step polymerization method, and high-performance polyoxamides have been successfully synthesized. [24][25][26][27][28][29] Comonomers are commonly utilized in polyamides to change the melt temperature and improve the processability. In this way, random copolyamides can be easily prepared.…”
mentioning
confidence: 99%
“…As poliamidas destacam-se entre os polímeros de engenharia por sua boa resistência química e à abrasão, boa resistência ao impacto e à flexão, alta resistência à fadiga e baixo coeficiente de atrito (DONG et al, 2017). Em contrapartida, as poliamidas são higroscópicas e sua estabilidade dimensional é inferior aos demais polímeros de engenharia, afetando as dimensões do produto final, uma vez que ocorre o inchamento do material após a absorção de água (PREDA et al, 2015).…”
Section: Introductionunclassified